2017
DOI: 10.1097/rti.0000000000000256
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in Chronic Thromboembolic Pulmonary Hypertension

Abstract: Chronic thromboembolic pulmonary hypertension (CTEPH) is one of the potentially curable causes of pulmonary hypertension and is definitively treated with pulmonary thromboendartectomy. CTEPH can be overlooked, as its symptoms are nonspecific and can be mimicked by a wide range of diseases that can cause pulmonary hypertension. Early diagnosis of CTEPH and prompt evaluation for surgical candidacy are paramount factors in determining future outcomes. Imaging plays a central role in the diagnosis of CTEPH and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 113 publications
0
38
0
Order By: Relevance
“…Several studies have shown substantial correlation between lung iodine density and perfusion, with comparable results to V/Q scans (82)(83)(84)(85). To date, DECT role in thoracic imaging has mainly targeted at pulmonary embolic disease and PAH (61,(86)(87)(88).…”
Section: Dual-energy Computed Tomography (Dect)mentioning
confidence: 90%
See 2 more Smart Citations
“…Several studies have shown substantial correlation between lung iodine density and perfusion, with comparable results to V/Q scans (82)(83)(84)(85). To date, DECT role in thoracic imaging has mainly targeted at pulmonary embolic disease and PAH (61,(86)(87)(88).…”
Section: Dual-energy Computed Tomography (Dect)mentioning
confidence: 90%
“…In mosaic perfusion, decreased attenuation is secondary to hypoperfusion distal to the occluded/suboccluded arteries, whereas increased attenuation is related to redistribution of blood flow to patent vessels. In areas of increased attenuation, larger vessels and stronger enhancement after contrast material administration can be seen (60,61,74) (Figure 8). Although more commonly seen in patients with CTEPH, mosaic lung attenuation is nonspecific, and may be also seen in patients with PH due to cardiac or lung disease (75).…”
Section: Lung Parenchyma Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Bands are linear structures that run along the long axis of a vessel and may appear in the setting of chronic PE. Webs are networks of bands that are often found at vessel bifurcations in chronic PE and are associated with distal neovasculature [13,92,93].…”
Section: Ct Pulmonary Angiography For Pre-procedural Planningmentioning
confidence: 99%
“…Computed tomography has been seen to have several technological advances over the last three decades, and the introduction of iterative reconstruction CT algorithms has led to a significant reduction in image noise and radiation dose [16]. CT is frequently used in the evaluation of breathlessness and in the assessment of lung and increasingly cardiac disease [17][18][19][20][21][22][23][24]. The majority of studies using CT as a diagnostic tool have concentrated primarily on pulmonary artery size.…”
Section: Introductionmentioning
confidence: 99%